Field hydrogeology a guide for site investigations and report preparation - Moore, John E. 1931- (CRC Press, 2012)
"In recent years, the focus in hydrogeologic investigations has expanded to include aquifer sustainability as part of resource evaluations. While there are other books on the subject, Field Hydrogeology: A Guide for Site Investigations and Report Preparation provides the first integrated presentation of the American Society of Testing Materials (ASTM) standards, US Geological Survey (USGS), and US Environmental Protection Agency (EPA) field techniques. It also includes access to a Web site that contains software for designing aquifer tests and aquifer-recharge experiments.Written by an author with more than 50 years of experience in hydrology and geology, this reference treats the subject from a field standpoint. Useful as a field guide or textbook, it contains standard methods for planning and undertaking hydrogeologic investigations.-It incorporates case studies, contains a glossary of field-hydrogeology technical terms, and provides a detailed list of ASTM standards and key hydrologic Web sites.The guide is based on ASTM standards as well as EPA and US Department of Interior field technical manuals. The text covers hydrogeologic fundamentals, conceptual models, planning an investigation, surface investigations, subsurface investigations, field inventory, stream flow measurements, water quality measurements, and report preparation. This revised and updated Second Edition also includes new material on the history of hydrogeology, field safety, aquifers, groundwater quality, hydrogeologic maps, and federal regulations.-It gives students and seasoned professionals a vast array of clearly written descriptive materials and an extensive source of references available at their fingertips.Whats New in This Second Edition: New chapter on the history of hydrogeologyNew chapter on groundwater development and management, including US federal regulations and transboundary aquifersNew material on field safety, groundwater quality and testing, and construction of hydrogeologic cross section and maps New international case studiesNew THEIS computer model to design aquifer testsUpdated information on latest principles and techniques"-- Provided by publisher.
Keywords: Hydrogeology -- Fieldwork.; elektronické knihy; electronic books